2015
DOI: 10.1007/s00126-015-0599-7
|View full text |Cite
|
Sign up to set email alerts
|

Sorption behavior of the Pt(II) complex anion on manganese dioxide (δ-MnO2): a model reaction to elucidate the mechanism by which Pt is concentrated into a marine ferromanganese crust

Abstract: It is difficult to directly investigate the chemical state of Pt in marine ferromanganese crusts (a mixture of hydrous iron(III) oxide and manganese dioxide (δ-MnO 2 )) because it is present at extremely low concentration levels. This paper attempts to elucidate the mechanism by which Pt is concentrated into marine ferromanganese crust from the Earth's continental crust through ocean water. In this investigation, the sorption behavior of the Pt(II) complex ions on the surface of the δ-MnO 2 that is a host of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 14 publications
3
21
0
Order By: Relevance
“…In addition, X-ray absorption near-edge structure and extended X-ray absorption fine structure measurements further indicate that redox-sensitive elements, such as Co, Ce and Te, which are found bound in hydrogenetic nodules and crusts, are present in a higher oxidation state than in the overlying ocean water. This observation confirms that the exceptionally high concentration of such metals in polymetallic nodules results from redox processes involving Mn oxide 31,35,60,64,65,68 . By contrast, other elements (such as Pb) remain divalent during surface adsorption and incorporation 68 .…”
Section: Formation Controls On Nodule Chemistry the Mn Oxidessupporting
confidence: 77%
See 1 more Smart Citation
“…In addition, X-ray absorption near-edge structure and extended X-ray absorption fine structure measurements further indicate that redox-sensitive elements, such as Co, Ce and Te, which are found bound in hydrogenetic nodules and crusts, are present in a higher oxidation state than in the overlying ocean water. This observation confirms that the exceptionally high concentration of such metals in polymetallic nodules results from redox processes involving Mn oxide 31,35,60,64,65,68 . By contrast, other elements (such as Pb) remain divalent during surface adsorption and incorporation 68 .…”
Section: Formation Controls On Nodule Chemistry the Mn Oxidessupporting
confidence: 77%
“…Recent synchrotron-based methods, such as X-ray absorption near-edge structure and extended X-ray absorption fine structure spectroscopy, built on prior statistical analysis, experimental work and thermodynamic models to demonstrate that metal enrichment and the structural incorporation of minor and trace metals in deep-ocean polymetallic nodules is controlled by the mineralogy of the nodule [60][61][62][63][64][65] . As a result, noduleformation processes -hydrogenetic versus diagenetic precipitation -that control the mineralogy of the polymetallic nodules also govern their chemical composition 1,2,39,41 .…”
Section: Formation Controls On Nodule Chemistry the Mn Oxidesmentioning
confidence: 99%
“…A DES complex can evolve into a triple-edge-sharing complex (TES) and incorporate progressively into the MnO 2 layer during the crystal growth. The identification of some of the surface species (INC, TCS, DCS, and DES) has led to accelerating research aimed to understand their thermodynamic stability and how the mineral structure, layer size, and chemical composition control the metal sorption selectivity and capacity per specific surface area. ,, …”
Section: Introductionmentioning
confidence: 99%
“…13. 58 In 2020, Koschinsky et al reported the Pt L2 and L3-edge XANES spectra for Pt adsorbed on FeOOH and δ-MnO2 and Pt in a natural marine ferromanganese crust. The results showed that Pt(II) adsorbed on FeOOH was not oxidized but was oxidized to Pt(IV) on δ-MnO2.…”
Section: •2•1 Platinum (Pt 4 F Xps Pt L3-edge Xas)mentioning
confidence: 99%